A design of a robust discrete-time controller. (May 2015) - Sakai, Kyohei; Shibasaki, Hiroki; Tanaka, Ryo; Murakami, Takahiro; Ishida, Yoshihisa
Abstract: In this paper, we proposed a robust discrete-time controller. This control system, which is derived from the idea of the normalized plant, does not include plant parameters. Thus, we obtain a control system independent of plant parameters and that has the same structure as a conventional optimal servo control system. Simulation and experimental results show that the proposed method is fairly robust to plant parameter variations and external disturbances. Abstract : Highlights: A design method for a robust discrete-time controller is proposed. The control system derived from the idea of the normalized plant does not include plant parameters. The proposed method can eliminate the influence of an input-side disturbance and is robust to parameter changes. The effectiveness of the proposed method is confirmed by simulation studies. We also confirm the effectiveness of the proposed method through an experiment with a DC motor.